2019
DOI: 10.1186/s12879-019-3697-9
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 polymorphism correlates with immune activation, CD4 decline and plasma IP10 levels in HIV patients

Abstract: BackgroundThe mechanism behind HIV mediated immune activation remains debated, although the role of virus replication in this process is increasingly evident. Toll like Receptor 9 (TLR9) has been implicated in HIV mediated immune activation via sensing of viral CpG DNA. Polymorphisms in the TLR9 gene and promoter region including TLR9 1635A/G and 1486C/T have been found to be associated with multiple infectious diseases and cancers.MethodsIn the current study, we looked at the correlation of TLR9 polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 68 publications
0
16
1
Order By: Relevance
“…TLR7 rs179008, TLR9 rs352140 were linked to the high viral loads and lower CD4 T-cell counts in Germany, Spanish, American cohort respectively. [ 43 , 44 , 58 ] However, above results were in contrast to findings of Said et al [ 57 ] These inconsistent findings may be due to ethnicity, sample size, or sampling error. Therefore, we need more research to expand the sample size for meta-analysis and ethnicity subgroup analysis to get more reliable conclusions.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…TLR7 rs179008, TLR9 rs352140 were linked to the high viral loads and lower CD4 T-cell counts in Germany, Spanish, American cohort respectively. [ 43 , 44 , 58 ] However, above results were in contrast to findings of Said et al [ 57 ] These inconsistent findings may be due to ethnicity, sample size, or sampling error. Therefore, we need more research to expand the sample size for meta-analysis and ethnicity subgroup analysis to get more reliable conclusions.…”
Section: Discussioncontrasting
confidence: 81%
“…[ 45 ] The results reporting of the influence of the TLR9 rs352140 on disease progression are contradictory. A study performed in Spain [ 43 ] and American [ 58 ] HIV-infected cohort showed that TLR9 rs352140 is associated with lower CD4 count and higher viral load as rapid progression. In contrast, study in Omani showed that TLR9 rs352140 is associated with high CD4T cell count.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these genes are associated with the cell cycle, apoptosis, lymphocyte migration, or CD4 + T‐cell homeostasis . Conversely, the CCR2 rs1799864‐AG genotypes, HLA‐A68 and HLA‐B15 alleles, TLR9 1635AA genotype, polymorphism rs1385129 in the glut1 gene SLC2A1, and polymorphisms in the IFN‐γ and IL19 genes are linked to poor CD4 + T‐cell recovery in HIV‐1‐infected individuals.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…1635AA genotype, 192 polymorphism rs1385129 in the glut1 gene SLC2A1, 193 and polymorphisms in the IFN-and IL19 genes 194 are linked to poor CD4 + T-cell recovery in HIV-1-infected individuals.…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…Sex differences in TLR9 expression has also been reported in mice, where male mice showed higher expression of TLR9 and higher activation of innate immune system with higher numbers of infiltrating neutrophils upon MCMV viral infection but similar viral load between male and female ( Traub et al, 2012 ). Research performed in HIV patients furthermore showed that TLR9 stimulation by viral CpG DNA contributes to HIV immunopathogenesis and the TLR9 polymorphisms 1635A/G and 1486C/T being associated with disease progression ( Joshi et al, 2019 ). Differences in adverse outcome of Covid-19 between ethnic groups may also in part result from genetic predisposition.…”
Section: Multidisciplinary Clues That Reason the Proposed Role For Tlmentioning
confidence: 99%